ChemInform Abstract: Efficient and Productive Asymmetric Michael Addition: Development of a Highly Enantioselective Quinidine‐Based Organocatalyst for Homogeneous Recycling via Nanofiltration. Issue 27 (13th June 2013) - Siew, Weiming Eugene; Ates, Celal; Merschaert, Alain; Livingston, Andrew G.
Abstract A series of enlarged quinidine‐derived organocatalysts are synthesized based on the concept of polyalkylation.